2002
DOI: 10.1111/j.0889-7204.2002.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

Small LDL and Its Clinical Importance as a New CAD Risk Factor: A Female Case Study

Abstract: The underlying metabolic cause of coronary heart disease in many patients is not high blood cholesterol. In fact, the Framingham study has reported that 80% of individuals who go on to have coronary artery disease have the same total blood cholesterol values as those who do not go on to have a cardiovascular event. The most common metabolic contributor to coronary artery disease is the atherogenic lipoprotein profile, characterized by an abundance of highly atherogenic small, dense low-density lipoprotein part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…LDL cholesterol is often called bad cholesterol because it tends to form deposits in the walls of arteries while circulating through the bloodstream, decrease artery diameter, and result in atherosclerosis. 27 On the contrary, HDL cholesterol is referred to as good cholesterol because it can maintain the healthy state of the inner blood vessel walls by scavenging and recycling cholesterol through transporting it to the liver where it can be reprocessed. [28][29][30] Accordingly, CVD risk indicators such as AI and CRI are measured from the blood levels of LDL cholesterol, HDL cholesterol, and T-CHO.…”
Section: Discussionmentioning
confidence: 99%
“…LDL cholesterol is often called bad cholesterol because it tends to form deposits in the walls of arteries while circulating through the bloodstream, decrease artery diameter, and result in atherosclerosis. 27 On the contrary, HDL cholesterol is referred to as good cholesterol because it can maintain the healthy state of the inner blood vessel walls by scavenging and recycling cholesterol through transporting it to the liver where it can be reprocessed. [28][29][30] Accordingly, CVD risk indicators such as AI and CRI are measured from the blood levels of LDL cholesterol, HDL cholesterol, and T-CHO.…”
Section: Discussionmentioning
confidence: 99%
“…[1819] Monounsaturated fatty acids (MUFAs) are predominant in olive oil, and have received increased attention as being potentially beneficial because of their association with low rates of coronary heart disease (CHD) in olive oil consuming populations of the Mediterranean basin. [20] Recommendations to decrease the intake of saturated fatty acids (SFAs) have been as a goal in prevention of CAD. In PIVUS study, a Swedish cross-sectional population based study of healthy elderly men and women, failed to identify a relationship between levels of SFAs in cholesteryl esters and high sensitivity-CRP (hs-CRP) concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a 8-week hypercholeterolemic human trial with 120 mg/day T3 supplementation was conducted in Japan to evaluate the impact of the two most potent T3 isomers on serum cholesterol, triglycerides, LDLcholesterol, and HDL-cholesterol. Since LDL particles vary in size/density, and studies have shown that smalldense LDL (sd-LDL) particles equate to a higher risk factor for coronary heart disease than larger and less dense LDL particles 21) , we further evaluated whether T3 supplementation impacted the 20 fractions of triglycerides and cholesterol lipoproteins of various size/density 22) .…”
Section: Introductionmentioning
confidence: 99%